COMPARISON OF THE KEY ECONOMIC STIMULUS PROPOSALS TO ACHIEVE THE RUSSIAN GDP GROWTH RATES ABOVE THE WORLD AVERAGE - A. O. Alekhnovich (Финансы: теория и практика)
At the Presidential meeting on economic issues held May 30, 2017, two programs of socio-economic development of Russia were presented. The program of the Center for Strategic Research (CSR) was developed in line with the traditional approach to the Russian economic management implemented over the past 17 years. The mid-term program of the Russian socio-economic development until 2025 under the name “The Growth Strategy” developed under the RF Presidential order No. Pr-1347 of July 14, 2016, at the initiative of the Stolypin club reflects a new look at the Russian economic policy that takes into account the experience of “economic miracle” countries and replicates successful experience of individual industries and regions of Russia that implies more active involvement of the available mechanisms for boosting the economic growth. At present, the above programs are subject to active debates and the question as to which approach will be adopted remains open. The paper presents a comparison table of key provisions of the two programs. The CSR program developed under the leadership of A. L. Kudrin was not presented for a broad discussion, so its analysis was carried out based on public statements made by A. L. Kudrin as well as individual presentation materials (presentation by A. L. Kudrin at the Gaidar Forum in 2017, at the April HSE conference in 2017 and at the Presidential meeting on May 30, 2017). In his directive towards the implementation of the President’s Message to the Federal Assembly No. 2346, paragraph 1 b) of December 5, 2016, the President set the task “to reach the Russian Federation economy growth rates exceeding the world economic growth rates not later than by 2019-2020” .To start the implementation of the economic policy as early as in 2018, a decision on which of the programs will be implemented must be made urgently.